Subjects and Subjectivities on-Line. Thought Processes - Sanchez, Luz Marilyn Ortiz (European Journal of Multidisciplinary Studies, 2018)
The characterization of the symbolic cyber-cultural exchanges in the world of the cyber-society as a socio-semiotic practice is determinant in the configuration of subjects and subjectivities, which show the new forms of social relations, and interactions in the actual global society, starting from the languages of cyber-culture. It is clear that contemporary societies have experienced deep transformations in a relatively short span, in comparing it with other epochs of humanity, as an outcome of the globalization process. One of them is the incessant flow techno-mediated of the information and communication than permeates and modify all the areas and social, cultural and educational practices. The cyberspace confronts the objective, universal, and true modern world with a border world, without spaces or time, from where a new presence arises projected from the virtual world; here languages come to life in the stage of a new expressive medium, body and subjectivity are the protagonists. There is a lot to say about the cyber-culture, not only about the technological impact, but also about the modes of subjectivity created, starting from the multi-presence of bodies on line generated in this symbolic space.
Keywords: Cyber-culture. Episteme. Subject and Subjectivities.